Effects of CRISPR/Cas9-mediated stearoyl-Coenzyme A desaturase 1 knockout on mouse embryo development and lipid synthesis - Tian,Huibin; Niu,Huimin; Luo,Jun; Yao,Weiwei; Gao,Wenchang; Wen,Yang; Cheng,Min; Lei,Anmin; Hua,Jinlian (PeerJ, 2022)
Background Lipid synthesis is an indispensable process during embryo and growth development. Abnormal lipid synthesis metabolism can cause multiple metabolic diseases including obesity and hyperlipidemia. Stearoyl-Coenzyme A desaturase 1 (SCD1) is responsible for catalyzing the synthesis of monounsaturated fatty acids (MUFA) and plays an essential role in lipid metabolism. The aim of our study was to evaluate the effects of SCD1 on embryo development and lipid synthesis in a knockout mice model. Methods We used the CRISPR/Cas9 system together with microinjection for the knockout mouse model generation. Ten-week-old female C57BL/6 mice were used for zygote collection. RNase-free water was injected into mouse zygotes at different cell phases in order to select the optimal time for microinjection. Five sgRNAs were designed and in vitro transcription was performed to obtain sgRNAs and Cas9 mRNA. RNase-free water, NC sgRNA/Cas9 mRNA, and Scd1 sgRNA/Cas9 mRNA were injected into zygotes to observe the morula and blastocyst formation rates. Embryos that were injected with Scd1 sgRNA/Cas9 mRNA and developed to the two-cell stage were used for embryo transfer. Body weight, triacylglycerol (TAG), and cholesterol in Scd1 knockout mice serum were analyzed to determine the effects of SCD1 on lipid metabolism. Results Microinjection performed during the S phase presented with the highest zygote survival rate (P < 0.05). Of the five sgRNAs targeted to Scd1, two sgRNAs with relatively higher gene editing efficiency were used for Scd1 knockout embryos and mice generation. Genome sequence modification was observed at Scd1 exons in embryos, and Scd1 knockout reduced blastocyst formation rates (P < 0.05). Three Scd1 monoallelic knockout mice were obtained. In mice, the protein level of SCD1 decreased (P < 0.05), and the body weight and serum TAG and cholesterol contents were all reduced (P < 0.01).
Keywords: Stearoyl-Coenzyme A desaturase 1; CRISPR/Cas9; Knockout mouse; Embryo development; Lipid synthesis